Histological Analysis of Langerhans Islets and β-Cell Morphology in Diabetic Rats Treated with Bischofia javanica Nanoherbal - Silaen, Srinatalia; Silaban, Irving; Sitepu, Christina Sitepu; Rumahorbo, Cheryl Grace Pratiwi (Talenta Publisher, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder marked by hyperglycemia and β-cell damage. Standard therapies like metformin reduce blood glucose but rarely restore pancreatic structure. Bischofia javanica leaves, rich in flavonoids and phenolics, have traditional antidiabetic use with antioxidant and anti-inflammatory potential. This study evaluated the effects of nanoherbal B. javanica on pancreatic histopathology in streptozotocin (STZ)-induced diabetic rats. Thirty male Wistar rats were divided into six groups: negative control (KN), positive control (KP), metformin 150 mg/kg BW (KS), and nanoherbal B. javanica at 50 mg/kg BW (P1), 100 mg/kg BW (P2), and 200 mg/kg BW (P3). Pancreatic tissues were examined using hematoxylin-eosin staining and analyzed with the Pancreatic Injury Severity Score (ISS). Results showed that KP developed severe damage with the highest ISS (2.86), characterized by islet shrinkage, β-cell degeneration, insulitis, fibrosis, and vascular abnormalities. KS showed moderate improvement (ISS 1.71), while nanoherbal treatment groups exhibited dose-dependent recovery. P3 (200 mg/kg BW) achieved near-normal morphology with the lowest ISS (0.71), demonstrating superior effects compared to KS. These findings suggest that nanoherbal B. javanica protects and regenerates pancreatic β-cells through antioxidant and anti-inflammatory mechanisms, while nanoformulation enhances bioavailability and therapeutic efficacy of its active compounds.